Diagnosis Kesulitan Belajar Matematika Siswa Kelas V di Madrasah Ibtidaiyah Munawariyah Palembang - Mardiah Astuti; Tutut Handayani (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2019)
This research aims to find out the difficulties of students in learning subject of arithmetic operations in class VB of Ibtidaiyah Munawariyah Palembang, to see the factors that caused the difficulties of students when studying mathematics in the VB class of Palembang Ibtidaiyah Munawariyah, and also for knowing the efforts made by the mathematics teacher in overcoming the difficulties of students in the VB class of Palembang Madrasah Ibtidaiyah Munawariyah. This research is guided by qualitative descriptive methods. The results shows that, first, the difficulties of students in learning subject of arithmetic operations in class VB of Ibtidaiyah Munawariyah Palembang are inability of students in mastering mathematic concepts correctly, inability of students to count, inability of students to understand mathematical symbols, and inability students in understanding multiplication. Second, the factors that caused the difficulties of students when studying mathematics are: (1) internal factors that students have low intellectual ability and tend to be lazy in studying mathematics thus it can cause students to make mistakes in working on the problem. (2) external factors that caused the difficulties of students in learning subject of arithmetic operations are lack of support that given by teachers and family, and noisy school environment. Third, the efforts made by mathematics teachers in overcoming the difficulties of students in learning subject of arithmetic operations are the need of special teaching such as tutoring, using innovative and creative media or teaching methods to facilitate students, and creating conditioning (reinforcement, rewards, encouragement), and drill. Keywords : Diagnosis, difficulties, learning